(untitled) (Annals of Medical Research, 2021)
Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus, which is detected by the transmission from bat to person in Wuhan Province of China, has shown its effect all over the world in a very short time. There is no treatment method proven effective in Coronavirus disease 2019 (COVID-19) pandemics. The whole world is still working on it. Convalescent Plasma (CP) treatment is a passive antibody treatment that has been shown to be effective during periods of epidemic disease in history. CP treatment is interesting in the treatment of virus infection without vaccine or specific treatment, such as SARS-CoV-2, which causes COVID-19. The mechanisms of action of CP include neutralizing the virus by direct binding, initiating virus elimination by complement activation, antibody-dependent cellular cytotoxicity and / or phagocytosis. Neutralizing antibodies are the most important mechanisms of action. The most important point in recovery is the inactivation of the virus and the prevention of viral replication. It was demonstrated for the first time that CP significantly reduced mortality in COVID-19 disease. Our results of CP treatment in COVID-19 patients have been published. We have shown that CP is effective and safe in COVID-19 disease. We aimed to gather CP experiences up to date in COVID-19.